Systematic Implementation of Technology-Enhanced Learning Management - Sudibya, Jarmanta; Prasojo, Lantip Diat (Journal of Innovation and Research in Primary Education, 2025)
Technology-enhanced learning management has become essential for vocational schools to prepare students for digitalized workforces. However, systematic implementation approaches and their impacts on educational quality remain underexplored in vocational education contexts. This qualitative case study examined technology-enhanced learning management implementation across three state vocational schools in Tanjung Selor District, Indonesia. Data were collected through in-depth interviews with principals, curriculum coordinators, and teachers, direct observations of learning processes, and document analysis. The Miles, Huberman, and Saldaña model guided data analysis through systematic coding and thematic development. All schools implemented a five-stage framework: planning (including diagnostic assessment and industry partnerships), infrastructure preparation, human resource development, technology implementation, and evaluation. Distinct technology integration models emerged: Teaching Factory (SMK N 1), industry classes and simulation-based learning (SMK N 2 and N 3), and artificial intelligence integration (SMK N 2). Positive impacts included enhanced student engagement, improved teacher creativity, and strengthened industry connections. Challenges encompassed technology gaps, access inequalities, equipment limitations, staff readiness variations, technology misuse, and budget constraints. Schools demonstrated organizational resilience through strategic partnerships, systematic professional development, and positive culture initiatives. The systematic implementation approach aligns with adaptive teaching theory and contemporary change management frameworks. The diversity of technology integration models reflects institutional capacity to contextualize innovations according to specializations. However, technology integration introduces complex classroom management challenges requiring sophisticated pedagogical competencies beyond traditional teaching skills.